AIDS : opposing viewpoints - Biskup, Michael D., 1956-; Swisher, Karin, 1966- (San Diego, CA : Greenhaven Press, 1992)
Includes articles that present different viewpoints on such aspects of AIDS as the seriousness of the problem, moral issues, prevention, and treatment. Includes critical thinking activities.
Includes bibliographical references (p. 206-208) and index.
Savar campus library
Keywords: AIDS (Disease) -- Social aspects; AIDS (Disease).; Critical thinking